2013
DOI: 10.1177/1938640013507105
|View full text |Cite
|
Sign up to set email alerts
|

Total Dislocation of the Talus

Abstract: Total talar dislocation is a rare injury that is usually open. We report a case of closed anterolateral dislocation in a 19 year old, following a fall from a bicycle. He was treated with prompt closed reduction. A magnetic resonance imaging scan 6 months later showed no signs of avascular necrosis. At 2 years follow-up, the patient had a full, pain free, range of motion at the ankle and subtalar joints.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 14 publications
(29 reference statements)
0
4
0
Order By: Relevance
“…In our report, the patient had his foot in supination on landing resulting in a closed anterolateral total talar dislocation (TTD). Most of these patients are treated by immediate closed reduction [15], however in our case this could not be achieved due to extensor digitorum brevis blocking the reduction.…”
Section: Discussionmentioning
confidence: 74%
“…In our report, the patient had his foot in supination on landing resulting in a closed anterolateral total talar dislocation (TTD). Most of these patients are treated by immediate closed reduction [15], however in our case this could not be achieved due to extensor digitorum brevis blocking the reduction.…”
Section: Discussionmentioning
confidence: 74%
“…However, the treatment methods reported for such injuries are controversial. 1,7,21,22 The most common treatments include closed reduction with external fixation, open reduction with internal fixation, talar excision, arthrodesis, etc. (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…These are of great significance for assessing damage and therefore guiding treatment and prognosis. However, the treatment methods reported for such injuries are controversial 1,7,21,22 . The most common treatments include closed reduction with external fixation, open reduction with internal fixation, talar excision, arthrodesis, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Previous authors have suggested early total or partial talectomy 5 ; however, subsequent research has shown that such aggressive measures are unneeded. 1 - 3 , 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 The present study chronicles the authors' experience treating a checkrein deformity that resulted from a closed pantalar dislocation. To our knowledge, this study is the first to report such a deformity occurring after this injury.…”
mentioning
confidence: 81%